Data collection tool for stakeholders’ mapping (AR) - Ouerghemmi, Hassen; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
This research tool is a stakeholder matrix based on pre-defined outreach queries aimed at performing the stakeholder mapping that will feed into the social network analysis. The coherent understanding of the structure of a given sector or value chain is obtained by collecting data on the actors present, their functions and the relationships between them, which this matrix allows. The questions contained in the matrix are designed to provide comprehensive descriptions of each actor's role, connections, and power in the system. By allowing such responses to be obtained from different respondents, the matrix makes it possible to identify different types of actors and collaborations, as well as patterns of interaction that characterize a particular sector.